2009
DOI: 10.1380/ejssnt.2009.459
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Tribological Performance of Diamond-Like Carbon Based Coatings for Aerospace Component Processing

Abstract: This work examines diamond-like carbon (DLC) coatings deposited by plasma enhanced chemical vapour deposition (PECVD) as an environmentally friendly alternative to chromium plating in restoration of worn or damaged aircraft components. DLC coatings offer superior mechanical properties; however, high internal stresses and poor adhesion can prevent the deposition of thick films. This work examines a series of layered structures based on epoxy-resin interlayers with DLC applied as a surface film. Wear testing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…The high initial COF value for all conditions was due to the adhesion wear that occurred between the coated samples and the ball. Also, it is important to point out that the coefficient of friction values obtained in this study showed values lower than values obtained from Cr coatings by previous researchers [ [40] , [41] , [42] , [43] ], which invariably connotes better wear resistance. This signifies an improved adhesion of the electrodeposited Cr coating to the SS substrate, and this improvement could be attributed to the new pretreatment method (anodic activation) developed in this study.…”
Section: Resultscontrasting
confidence: 64%
“…The high initial COF value for all conditions was due to the adhesion wear that occurred between the coated samples and the ball. Also, it is important to point out that the coefficient of friction values obtained in this study showed values lower than values obtained from Cr coatings by previous researchers [ [40] , [41] , [42] , [43] ], which invariably connotes better wear resistance. This signifies an improved adhesion of the electrodeposited Cr coating to the SS substrate, and this improvement could be attributed to the new pretreatment method (anodic activation) developed in this study.…”
Section: Resultscontrasting
confidence: 64%
“…Coupled with the ability to deposit conformal coatings on various substrates, enables the fabrication of compact and portable IR sensors with reduced form factors and known protection and thermal management benefits [8]. This makes hydrogenated carbon thin films ideal for emerging applications such as wearable electronics, unmanned aerial vehicles (UAVs), and Internet of Things (IoT) devices [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this direction DLC materials are good candidates for capacitors implementation [4]. Moreover, due to their superior mechanical properties, the DLC materials can be used as coating systems in restoring aircraft components [5].…”
Section: Introductionmentioning
confidence: 99%